Re-Design Layout and Allocation of Raw Material Warehouses Using Simulation Methods to Minimize the Handling Cost from Port to Warehouses - Boy Cahyo Prihanto; I Nyoman Pujawan (IPTEK Journal of Proceedings Series, 2020)
The high cost of raw materials handling from the port to the warehouses at PT. Petrokimia Gresik has encouraged this research to find solutions to reduce costs in raw material unloading activities. The location of factories and raw material warehouses that are separated from each other, the number of warehouses that are not yet connected with conveyor belts as well as the diverse types of raw materials become its own challenges in operating unloading activities to be more efficient. The layout and allocation of raw materials in the existing warehouses creates high cost of raw materials handling because slow moving raw materials are close to the production location, while fast moving raw materials are far from the production location. In addition, the differences in the existing unloading methods also affect the cost of raw materials unloading, the use of vessel cranes and dump trucks will increase costs, otherwise the use of conveyor belts will minimize the cost of raw materials handling. This research is important to find the layout and allocation of raw materials that have the most efficient handling costs. The steps in this study include (1) data collecting and processing; (2) making conceptual and simulation models, (3) verification and validation tests; (4) developing alternative scenarios; (5) running simulations based on alternative scenarios; (6) comparing scenarios using anova test and cost and benefit analysis. The simulation is done using Arena 14.0 software. The simulation results show that the re-design layout and allocation of 5 warehouses in Factory 2A and Factory 2B is the best alternative scenario. This scenario is proven to be able to minimize the cost of raw materials handling with savings of Rp. 10.958.028.455 per year with an ROI of 108% and a Payback Period of 0,48 years.